2003
DOI: 10.2307/1558761
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Policy and the Skills of Immigrants to Australia, Canada, and the United States

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(78 citation statements)
references
References 11 publications
2
72
2
2
Order By: Relevance
“…This chapter updates previous research exploring the potential for selection criteria, income-support policy and labour market conditions to facilitate entry into the Australian labour market (see Cobb-Clark, 2003). That research assessed initial outcomes (six months after migration) and concluded that the substantially improved outcomes for new arrivals over the 1990s resulted largely from changes in selection policy that led to enhanced skills amongst new immigrants.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…This chapter updates previous research exploring the potential for selection criteria, income-support policy and labour market conditions to facilitate entry into the Australian labour market (see Cobb-Clark, 2003). That research assessed initial outcomes (six months after migration) and concluded that the substantially improved outcomes for new arrivals over the 1990s resulted largely from changes in selection policy that led to enhanced skills amongst new immigrants.…”
mentioning
confidence: 68%
“…Australian labour markets and the dissimilarities in their immigration policies to shed light on the ways in which selection criteria might matter (see Chiswick, 1987;Duleep and Regets, 1992;Borjas, 1993;Antecol, et al, 2003a;2003b). These cross-national comparisons highlight the important role of the national origin mix in determining the skill level of the overall immigrant stream.…”
mentioning
confidence: 99%
“…In France, the Ministry of Labor established in 2002 a system to induce highly skilled workers from outside the EU to live and work in France. Given the apparent demographic problems and the aging of populations, the intensity of the brain drain could increase further during the next decades 2 . What are the consequences for sending countries?…”
Section: Introductionmentioning
confidence: 99%
“…introduced in these countries since the 1980s: point-systems favoring educated migrants were first put in place in Australia and Canada in the early 1980s, and it has been argued that such point-systems explain the higher quality of immigrants to Canada or Australia compared to the US, even after controlling for country of origin (Antecol et al, 2000). The US has also introduced programs to raise the number of skilled professionals and highly educated migrants (H1-B visa programs in the late 1980s), but the US immigration policy is still dominantly targeted towards family reunion and asylum seekers.…”
Section: Introductionmentioning
confidence: 99%